ANALISIS FLYPAPER EFFECT PADA BELANJA DAERAH KOTA DAN KABUPATEN DI INDONESIA - Fachruzzaman, Fachruzzaman; Suranta, Eddy; Martini, Elvi (JURNAL FAIRNESS, 2015)
The aims of local autonomy is to achieve local independence funding, so that the areas can organize themselves without any central government interference. The direct implications for the implementation of the above is needed great for adequate funding. Local government's main funding source, comes from the PAD and othe PAD which is used to finance all expenditures and development. But in some of the current and multi years funding sources not only from the PAD. Local governments also get help from central government transfers such as Equalization Fund in this case is General Allocation Fund (DAU) The aim of this research is to analyse influences of DAU and PAD’s to district’s spending in Indonesia. The samples of this research are taken from the budget report of Kabupaten/Kota within the Province of Sumatera and Java and used 15 province in the periode 2010-2012. Testing to all hypothesis done with SmartPLS. The results show that DAU and PAD partially as well as collectively have indeed influenced the realisation of budget. Furthermore, we might conclude from the results that there has been a flypaper effect which is showed by the DAU which has higher ability to predict district’s spending than the PAD.